Northern lights on the Dead Sea scrolls : proceedings of the Nordic Qumran Network 2003-2006 - Petersen, Anders Klostergaard. (Studies on the Texts of the Desert of Judah, 2009)
Structured by four important themes, the book discusses various aspects pertaining to the interpretation of the Dead Sea Scrolls. The first theme is comprised by a number of essays that deal with different aspects of textual interpretation of particular Qumran writings. The second theme centers on the question of historical referentiality. How can the purported referentiality of particular Qumran writings be used in order to reconstruct an underlying historical reality? The third theme includes essays that pertain to different dimensions concerning the methodology of interpretation. The fourth theme focuses on problems relating to the textual reconstruction of specific Qumran texts. In the final section of the book, the perspective is widened to other writings outside the more specific Qumran context.